Description Of Perceptions About Marriage Adjustment In Early Adult Individuals - Novita Maulidya Jalal (International Journal of Education, Vocational and Social Science, 2023)
This study aims to describe the perceptions of marriage from individuals who are in their early adulthood and adjustments to the marriage problems they face. This study uses a qualitative research method, namely by interview. Based on interviews that have been conducted on two subjects who are married in early adulthood, it gives a picture of marriage as the beginning of a new life, as well as the first step to becoming parents. The subjects of this study consisted of 2 people who were early adults. The results showed that the subject's perception of marriage was that the subject considered marriage as one of the best steps to have children and form a family. The subject also stated that in marriage there are things that are easy to learn such as the subject does not experience difficulties in adapting to his partner's family. However, the subject also considers that marriage also has challenges, namely obstacles at the beginning of marriage such as dividing time with education and the economy. The two subjects also said that adjustment to partners was carried out by building communication and mutual acceptance of differences between partners.